The Use Of Implicit Evidence For Relevance Feedback In Web Retrieval - White, Ryen W.; Ruthven, Ian; Jose, Joemon M. (24th BSC-IRSG European Colloquium on IR Research (ECIR 2002), Glasgow, Scotland, United Kingdom, 2002)
In this paper we report on the application of two contrasting types of relevance feedback for web retrieval. We compare two systems; one using explicit relevance feedback (where searchers explicitly have to mark documents relevant) and one using implicit relevance feedback (where the system endeavours to estimate relevance by mining the searcher's interaction). The feedback is used to update the display according to the user’s interaction. Our research focuses on the degree to which implicit evidence of document relevance can be substituted for explicit evidence. We examine the two variations in terms of both user opinion and search effectiveness.